Amyloid persistence in decellularized liver: biochemical and histopathological characterization. (2nd January 2016) - Mazza, Giuseppe; Simons, J. Paul; Al-Shawi, Raya; Ellmerich, Stephan; Urbani, Luca; Giorgetti, Sofia; Taylor, Graham W.; Gilbertson, Janet A.; Hall, Andrew R.; Al-Akkad, Walid; Dhar, Dipok; Hawkins, Philip N.; et al.
Abstract: Systemic amyloidoses are a group of debilitating and often fatal diseases in which fibrillar protein aggregates are deposited in the extracellular spaces of a range of tissues. The molecular basis of amyloid formation and tissue localization is still unclear. Although it is likely that the extracellular matrix (ECM) plays an important role in amyloid deposition, this interaction is largely unexplored, mostly because current analytical approaches may alter the delicate and complicated three-dimensional architecture of both ECM and amyloid. We describe here a decellularization procedure for the amyloidotic mouse liver which allows high-resolution visualization of the interactions between amyloid and the constitutive fibers of the extracellular matrix. The primary structure of the fibrillar proteins remains intact and the amyloid fibrils retain their amyloid enhancing factor activity.